Multiply and simplify: (6x + 3y)(6x − 3y)

Question

Multiply and simplify: (6x + 3y)(6x − 3y)

in progress 0
Isabelle 3 months 2021-10-19T23:13:59+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-19T23:15:32+00:00

    Answer:

    36x² – 9y²

    Step-by-step explanation:

    (6x + 3y)(6x − 3y)

    (6x)² – (3y)²

    36x² – 9y²

    0
    2021-10-19T23:15:40+00:00

    Answer:

    36x² – 9y²

    Step-by-step explanation:

    We see that the given expression (6x + 3y)(6x – 3y) looks just like the expression (a + b)(a – b). When multiplied out, this is a difference of squares identity that I highly recommend you memorise:

    (a + b)(a – b) = a² – b²

    Here, a = 6x and b = 3y, so plug these in:

    (6x + 3y)(6x – 3y) = (6x)² – (3y)² = 36x² – 9y²

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )